The role of cyclic AMP production, calcium channel activation and enzyme activities in the inhibition of testosterone secretion by amphetamine - Tsai, Shiow-Chwen (1997)
1. The aim of this study was to investigate the mechanism by which amphetamine exerts its inhibitory effect on testicular interstitial cells of male rats. 2. Administration of amphetamine (10(−12)–10(−6) M) in vitro resulted in a dose-dependent inhibition of both basal and human chorionic gonadotropin (hCG, 0.05 iu ml(−1))-stimulated release of testosterone. 3. Amphetamine (10(−9) M) enhanced the basal and hCG-increased levels of adenosine 3′:5′-cyclic monophosphate (cyclic AMP) accumulation in vitro (P<0.05) in rat testicular interstitial cells. 4. Administration of SQ22536, an adenylyl cyclase inhibitor, decreased the basal release (P<0.05) of testosterone in vitro and abolished the inhibitory effect of amphetamine. 5. Nifedipine (10(−6) M) alone decreased the secretion of testosterone (P<0.01) but it failed to modify the inhibitory action of amphetamine (10(−10)–10(−6) M). 6. Amphetamine (10(−10)–10(−6) M) significantly (P<0.05 or P<0.01) decreased the activities of 3β-hydroxysteroid dehydrogenase (3β-HSD), P450c17, and 17-ketosteroid reductase (17-KSR) as indicated by thin-layer chromatography (t.l.c.). 7. These results suggest that increased cyclic AMP production, decreased Ca(2+) channel activity and decreased activities of 3β-HSD, P450c17, and 17-KSR are involved in the inhibition of testosterone production induced by the administration of amphetamine.